Authoritarianism and necropolitical creation of martyr icons by Kemalists and Erdoganists in Turkey. (15th March 2022) - Yilmaz, Ihsan; Erturk, Omer
ABSTRACT: One of the most widely used and influential ways of creating foundational myths for authoritarian legitimation is to construct a necropolitical narrative around the significance of dying for the nation, homeland, state and the leader, i.e. martyrdom. Mbembe's concept 'necropolitics' (the right of the sovereign to determine who shall live and who shall die) has been expanded to include the pollical instrumentalization of martyrdom narratives. However, the literature has not analyzed the necropolitical martyr-icons. This paper aims to address this gap by looking at two historical episodes in Turkey, one in the 1930s dominated by secularists and post-2016 dominated by Islamists.